2014
DOI: 10.3126/ajms.v5i3.9593
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of some sex hormones concentrations by consumption of leaves extract of Viscum album (mistletoe) in rats

Abstract: Objective: This present study was conducted with the aim to investigate the effect of consumption of leaves extract of mistletoe on the concentration of some serum sex hormones (follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone and prolactin) in rats. Methods: Twenty-four (24) female albino Wistar rats (210-250 g final body weight) were randomly assigned into 4 groups of 6 rats each. Group 1 (control) took normal rat chow + drinking water. Group 2, extract treated-1 (ET-1), group 3, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…The results also agree with Ofem et al (2014) who suggested that leaves' extract of Viscum album contain potent agents with potentials to increase serum testosterone concentrations. The increase in testosterone levels may be due to some potent agents in the extract that stimulated the synthesis and subsequent release of these hormones in the anterior pituitary gland and ovary or probably promoted the cholesterol catabolism.…”
Section: Effect Of the Tested Compounds On Steroidal Level Hormonessupporting
confidence: 91%
“…The results also agree with Ofem et al (2014) who suggested that leaves' extract of Viscum album contain potent agents with potentials to increase serum testosterone concentrations. The increase in testosterone levels may be due to some potent agents in the extract that stimulated the synthesis and subsequent release of these hormones in the anterior pituitary gland and ovary or probably promoted the cholesterol catabolism.…”
Section: Effect Of the Tested Compounds On Steroidal Level Hormonessupporting
confidence: 91%
“…However, Uboh & co-investigators did not observe a significant increase in FSH and LH concentrations. Several investigators who evaluated different medicinal plants reported a similar increase in FSH and LH (Krishnamoorthy et al, 2013;Ofem et al, 2014;Onyegeme-Okerenta & Essien, 2015). It has been observed that as testosterone levels decrease, levels of FSH and LH are expected to increase to stimulate the production of more testosterone (Emanuele & Emanuele, 2001).…”
Section: Discussionmentioning
confidence: 85%
“…Ekstrenin 450 mg/kg uygulandığı grupta ise prolaktin hormonunun konsantrasyonu artarken LH, FSH ve testosteron hormonlarının konsantrasyonlarının azaldığı görülmüştür. Dolayısı ile bu bitkinin ovaryumun foliküler dinamiği üzerine iyileştirici etkileri saptanmıştır [36]. Kriyoprezerve fare spermi ile en iyi in vitro fertilizasyon oranı donmamış kontrollerde %62 bulunmuştur [13].…”
Section: Deney Hayvanlarında Bitkisel Kaynaklı Antioksidan Kullanımının Fertiliteye Etkisiunclassified